School Branding Management: Pengelolaan Merek melalui Kurikulum Berbasis Budaya Lokal Batik - Harisatunisa, Harisatunisa; Muslimah, Eksa (J-MPI (Jurnal Manajemen Pendidikan Islam), 2024)
A brand is an image as well as an identity for an educational institution. Thus the brand becomes one of the aspects that can encourage students to choose a school. The local cultural curriculum is one of the strengths for a school in building its uniqueness and identity. So it is common for educational institutions develop their school brand using local wisdom as a object. This study aims to narrate how brand management through a local culture-based curriculum at SMA N 1 Sokaraja is worked. A qualitative approach is used in this study. Data was collected through observation, interviews and documentation studies. Research subjects were selected using purposive sampling method. Principals, vice principals for curriculum and subject subject became participants in this study. The results of this study indicate that brand management is realized through Pendidikan Berbasis Keunggulan Lokal (PBKL) at SMA N 1 Sokaraja. The presence of PBKL as a brand identity has succeeded in forming a brand image by presenting symbolic benefits for students. This research can be used as a reference in creating a school brand development model in Banyumas.